Four-step phase-shifting digital holography simultaneously sensing dual-wavelength information using a monochromatic image sensor. (5th November 2015) - Tahara, Tatsuki; Mori, Ryota; Arai, Yasuhiko; Takaki, Yasuhiro
Abstract: Four-step phase-shifting digital holography simultaneously sensing dual-wavelength information from wavelength-multiplexed holograms is presented. Specific phase shifts for respective wavelengths are introduced to remove the crosstalk components and extract only the object wave at the desired wavelength from the holograms. Object waves at multiple wavelengths are selectively extracted by utilizing 2 π ambiguity and the subtraction procedures based on phase-shifting interferometry. Two-step phase-shifting interferometry is merged into the procedures to decrease the number of the recorded holograms. The proposed technique is numerically investigated and experimentally demonstrated. The applicability to the case where the number of wavelengths is more than two and possible noise when using two-step phase-shifting interferometry are discussed.